Pemberian Aromaterapi Lavender terhadap Penurunan Nyeri pada Ibu Pasca Sectio Caesarea Study Literature - Elvi Oktavia; Fathia Fakhri Inayati Said; Nurhidayah Amir; Ricky Riyanto Iksan; Roza Indra Yeni (Universitas Malahayati Lampung, 2022)
ABSTRACT The prevalence of normal delivery in Indonesia is 86.28%. (IDHS, 2018). Sectio caesarea (SC) surgery is carried out if there are complications, the priority is handling for the safety of the mother and baby. Physically this SC action causes pain in the abdomen. In this case, it is necessary to carry out pain management both pharmacologically and non-pharmacologically. In addition to painkillers, there needs to be a combination method with complementary therapy, namely Lavender Aromatherapy.To determine nursing interventions regarding the administration of lavender aromatherapy and its effect on reducing pain intensity in mothers after sectio caesarea from various journals. The design in this study is a Literature Review. Data Sources Search for research articles in the PubMed (2017-2021), Google Schoolar (2017-2021) and Garuda (2017-2021) databases. The research article search strategy uses the PICOS framework format with keywords: Aromatherapy Lavender